Determinants of Foreign Migration Destinations Selection in Nepali Rural Households - Kshetri, Tilak; Thapa-Parajuli, Resham (Journal of Development and Administrative Studies, 2022)
This paper examines the factors influencing rural Nepalese households’ preferences for selecting foreign migration destinations. The study utilizes panel data from the World Bank’s Nepal Household Risk and Vulnerability (NHRV) Survey from 2016 to 2018. We estimate a multinomial logistic regression to assess how household assets affect the choice of migration destinations, which include India, OECD countries, the Gulf region, and Asia. Our findings indicate that household asset accumulation is a crucial determinant of migration destination choice. Specifically, households with larger asset endowments are more likely to migrate to OECD countries, followed by the Gulf region, Asia, and India. The households with higher assets are more likely to migrate to the destinations offering possible higher wages, all else equal.